Removal ability of MTA-, bioceramic-, and resin-based sealers from obturated root canals, following XP-endo® Finisher R file: An ex vivo study - Taxiarchis G Kontogiannis; Nikolaos P Kerezoudis; Konstantinos Kozyrakis; Elefterios Terry. R. Farmakis (Wolters Kluwer Medknow Publications, 2019)
Aim: Removability assessment of mineral trioxide aggregate (MTA)-, bioceramic-, and epoxy resin-based sealers, with or without XP-endo® Finisher R file, was achieved. Materials and Methods: One hundred and twenty extracted single-rooted premolars were randomly organized into three equal groups, instrumented up to #40.04 and obturated with single-cone technique by gutta-percha and one of the following sealers: MTA Fillapex, TotalFill BC Sealer, or AH Plus. Following setting of the sealer, D-RaCe instruments were used in retreating all specimens. In half of the specimens, XP-endo® Finisher R file was additionally applied following D-RaCe, as a final step in retreatment. Working length (WL) following the procedure and patency were recorded. All specimens were split and observed for residuals under optical microscopy. Images were acquired, placed adjacent to each other forming continuous strips, and focus stacked with Helicon Focus software. A blinded observer evaluated all photographs. Analysis included Chi-square tests and one-way ANOVA. Results: WL was fully regained in all cases. Patency regaining (in terms of canal cleanness) was easier in AH Plus groups. Residuals were significantly more in TotalFill groups (P < 0.0001). XP-endo® Finisher R file improved removal only in the AH Plus subgroup. Conclusions: TotalFill residuals were harder to remove than those from MTA Fillapex or AH Plus groups. Patency is also harder to regain. XP-endo® Finisher R file had a positive removal influence only in the AH Plus subgroup.